Carbohydrates as Additives for the Formation of Isoporous PS‐b‐P4VP Diblock Copolymer Membranes. Issue 2 (7th December 2012) - Clodt, Juliana Isabel; Rangou, Sofia; Schröder, Anne; Buhr, Kristian; Hahn, Janina; Jung, Adina; Filiz, Volkan; Abetz, Volker
Abstract Highly porous polystyrene‐block‐poly(4‐vinylpyridine) (PS‐b‐P4VP) diblock copolymer membranes are prepared using carbohydrates as additives. Therefore α‐cyclodextrine, α‐(D)‐glucose, and saccharose (cane sugar) are tested for the membrane formation of three different PS‐b‐P4VP polymers. The addition of the carbohydrates leads to an increasing viscosity of the membrane solutions due to hydrogen bonding between hydroxyl groups of the carbohydrates and pyridine units of the block copolymer. In all cases, the membranes made from solution with carbohydrates have higher porosity, an improved narrow pore distribution on the surface and a higher water flux as membranes made without carbohydrates with the same polymer, solvent ratio, and polymer concentration.